(untitled) (CIPEEX, 2026)
INTRODUCTION: The adoption of Artificial Intelligence has transformed management and marketing in startups, optimizing decisions, personalization, and performance. Despite advances, technical, financial, and qualification challenges still limit its full implementation in the competitive organizational environment. OBJECTIVE: To investigate the impact of the use of Artificial Intelligence (AI) on strategic marketing decision-making in the startups studied, Mercado Livre and Amazon, aiming to identify the main advantages and challenges of this technology for the growth and competitiveness of these companies. METHOD: This study adopted a qualitative approach, through a bibliographic and exploratory review, analyzing recent scientific sources (2018-2025) on AI in marketing. It used thematic analysis to identify patterns, gaps, and trends, with strict selection criteria in databases such as SciELO and Scopus. RESULTS: AI has impacted strategic marketing in e-commerce through personalization and consumer experience, operational and logistical efficiency, and organizational, ethical, and regulatory barriers. It has enabled assertive campaigns, automation, and cost reduction, but faces cultural, professional, legal, and ethical challenges. CONCLUSION: The study showed that artificial intelligence has strongly impacted strategic marketing in e-commerce companies such as Amazon and Mercado Livre. AI optimizes decisions, automates processes, and personalizes campaigns, increasing competitiveness and efficiency. In addition to analyzing consumption patterns and trends, it still faces challenges related to continuous investment and ethics in the use of data.